Tinjauan Yuridis Terhadap Penyelesaian Perjanjian Wanprestasi dalam Gugatan Sederhana di Pengadilan Negeri Pamekasan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Because we are social creatures, laws establish norms about how members of society should interact with each other. The Constitution of the Republic of Indonesia establishes a legal framework to regulate all human interests, including human rights. An agreement is an important document that regulates the responsibilities and privileges of individuals involved in a contractual relationship. An agreement is defined as a legally binding act that binds the promising parties in Article 1313 of the Indonesian Civil Code. However, agreements are not always enforced, and defaults occur all the time; for example, PT. Bank Rakyat Indonesia (Persero) Tbk is fighting debtors who have not paid their bills. The causes of default, its impact on the parties, and the procedures required by law to resolve disputes are all discussed in this abstract. It is believed that a thorough understanding of default will help prevent similar incidents in the future and find fair and efficient solutions.